1975
DOI: 10.1080/03610737508257949
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in life satisfaction as a function of discrepancy between real and ideal self concepts

Abstract: Six age groups were compared with respect to discrepancy between real and ideal self concepts and the relationship between life satisfaction and discrepancy in self concepts. The subjects, ranging in age from 20 to 75 years, completed two self descriptive adjective rating scales which assessed real and ideal self concept and a life satisfaction index. Significant differences were found among age groups for real and ideal self concepts, life satisfaction, and discrepancy between real and ideal self concept scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
(3 reference statements)
2
4
0
Order By: Relevance
“…Using daily reports of mood and selfesteem, Diener and Emmons (1984) found that self-esteem correlated (across two studies) .46 and .34 with positive affect and -.40 and -.46 with negative affect. Similar results have been found in a national U.S. probability sample (Andrews, 1974), an adult married sample in the U.S. (Veroff, Feld, & Gurin, 1962), and by others (e.g., Czaja, 1975;Kozma& Stones, 1978;Pomerantz, 1978;Reid &Ziegler, 1980;Wilson, 1960).…”
supporting
confidence: 88%
“…Using daily reports of mood and selfesteem, Diener and Emmons (1984) found that self-esteem correlated (across two studies) .46 and .34 with positive affect and -.40 and -.46 with negative affect. Similar results have been found in a national U.S. probability sample (Andrews, 1974), an adult married sample in the U.S. (Veroff, Feld, & Gurin, 1962), and by others (e.g., Czaja, 1975;Kozma& Stones, 1978;Pomerantz, 1978;Reid &Ziegler, 1980;Wilson, 1960).…”
supporting
confidence: 88%
“…Of any variable that has been listed, self-esteem Is thought to be one of the most Important predictors of subjective happiness. This finding has been well reported In the research literature (Anderson, 1977;Czaja, 1975;Drumgoole, 1981;Glnandes, 1977;Hlgglns, 1978;Kozma & Stones, 1978;Peterson, 1975;Pomerantz, 1978;Raid & Zlegler, 1980;VanCoeverlng, 1974;Wilson, 1960). Campbell et al (1976) found self-esteem to be one of the highest correlations of any variable.…”
Section: Recent Studiessupporting
confidence: 83%
“…Within this category of social relationships is another type of variable, self-esteem. It was associated with successful social func tioning and feelings of happiness (Anderson, 1977;Czaja, 1975;Drumgoole, 1981;Glnandes, 1977;Higgins, 1978;Kozma & Stones, 1978;Peterson, 1975;Pomerantz, 1978;Reid & Zlegler, 1980;VanCoeverlng, 1974;Wilson, 1960).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Kuhlen reported that young people were happier, 63 while Andrews and Withey, 64 Alston et al, 27 and Spreitzer and Snyder 65 reported no age effect on happiness. However, Czaja, 66 Bortner and Hultsch, 67 Clemente and Sauer 28 and Medley 68 reported that old people were happier. Our results are in line with this general trend.…”
Section: Quality Of Life Measures and Basic Demographic Variablesmentioning
confidence: 99%